Toxicity of Citrus mitis, Citrus aurantifolia, and Citrus maxima leaf extract toward mortality of Aedes aegypti larvae (Diptera: Culicidae) - Hamidah, Hamidah; Adrianto, Hebert (KnE Life Sciences, 2017)
Dengue Fever is a significant health issue in Indonesia for it is always been found and unresolved since 1968. Dengue Fever is transmitted through mosquito (Aedes aegypti) bite. Resistance of mosquito larvae towards temephos as consequence of chemical larvicide consumption has been reported in several countries. One of safe and environmentally friendly efforts to control mosquito is by using herbal larvicide which produced from plants. This study examines methanol extract of Citrus mitis, Citrus aurantifolia, and Citrus maxima leaf toward mosquito larvae Ae. aegypti instar III for 24 hours. Data of larvae mortality is analyzed using probit analysis by SPSS software. The result shows that Citrus mitis has the highest toxicity with the lowest lethal concentrations (LC) that are LC50 = 1.547 ppm and LC90 = 3.328 ppm. It followed by Citrus aurantifolia and Citrus maxima respectively. Keywords: larvicide; Aedes aegypti; leaf extract; Citrus mitis; Citrus aurantifolia; Citrus maxima